A compact dual-grating wavemeter using signal processing - Yiming Wang; Yi Ma; Yu Huang; Zhanfeng Li; Xiaohu Yang (Results in Physics)
Spectral resolution is an important parameter of a wavemeter. Here, we propose a compact wavemeter based on two gratings and signal processing. By applying the Multiple Signal Classification (MUSIC) algorithm to process the sampled Talbot patterns and reconstruct the spectrum, we have demonstrated through simulations the capability to enhance spectral resolution. Overall, we present a compact wavemeter capable of improving resolution. Using this method, while maintaining the contrast of the Talbot patterns, the spectral resolution can reach 5 pm, which is higher than that of any currently reported Talbot wavemeters.